Spatial patterns of reef fishes and corals in the thermally extreme waters of Qatar - Bouwmeester, Jessica; Ben-Hamadou, Radhouane; Range, Pedro; Al Jamali, Fahad; Burt, John A. (Frontiers in Marine Science, 2022)
The Persian Gulf is a thermally extreme environment in which reef corals have adapted to survive through temperature ranges that would be lethal to corals from other regions. Despite offering a unique opportunity to better understand how corals from other regions may adapt in the future, through a changing climate, much of the Gulf coral and fish communities remain to be described. In the southwestern Gulf nation of Qatar few reef sites have been described to date. We here characterize reef communities from 16 sites around the Qatar Peninsula, encompassing depths from 3 to 25m. We found that the healthiest coral reefs communities to be in deeper offshore reefs, with high coral and fish species richness and high coral abundance, likely a result of their occurrence below summer thermocline depths and distance from urban pressures. In contrast, we found shallow reefs, both nearshore and offshore, to have low species richness and abundance relative to deeper reefs, presumably due to impacts from recurrent bleaching events and development pressures over recent decades. The results of this work underscore the Qatar Peninsula as being at the biogeographic epicenter of the wider Gulf. However, further temperature increases may push both fishes and corals over their physiological limits. Management efforts at both the regional and global level are needed to reduce thermal stressors and preserve the rich reef ecosystems found in the waters surrounding Qatar.